PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL WORDWALL BERBASIS KEARIFAN LOKAL JAWA TIMUR MATERI MEMBANGUN MASYARAKAT YANG BERADAB KELAS 4 - Maracintia; Anwar, Moh. Farid Nurul; Chotimah, Chusnul; Fitriyah, Siti Ni'matul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the suboptimal use of interactive digital media and the low level of student engagement in learning, resulting in a passive learning process and limited integration of local wisdom in classroom instruction. In fact, integrating local wisdom into learning media can make the material more contextual and meaningful for students. This study aims to develop and examine the validity and effectiveness of a Wordwall-based digital learning media integrated with East Java local wisdom. The research employed a Research and Development (R&D) method using the Borg and Gall model, simplified into nine stages: needs analysis, product design, product development, expert validation, revision, limited trial, field testing, effectiveness evaluation, and product finalization. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and pre-test and post-test instruments. The data were analyzed descriptively using percentages of validity and learning mastery. The results indicated that the media achieved a “very valid” category in terms of content, media design, and language aspects. The effectiveness test showed an increase in the average score from 70 in the pre-test to 91.80 in the post-test, and learning mastery reached 91.80% above the minimum mastery criteria (KKM). Therefore, the Wordwall-based learning media integrated with East Java local wisdom is considered valid and effective for IPAS learning in fourth-grade elementary school students.